Development of Islamic Integrated Mathematics Module Based on HOTS Problem (MATHIKS HOTS) with Strengthening Mathematical Literacy on SPLDV Material - Achmad Firmansyah; Mutiara Arlisyah Putri Utami (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to develop an Islamic-integrated mathematics module based on HOTS (Higher Order Thinking Skills) questions while strengthening mathematical literacy in the SPLDV topic. The research was conducted in Grade VIII at MTs Negeri Pasuruan City using a Research and Development (RD) approach with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The final product is a mathematics module called MATHIKS HOTS (Islamic-Integrated Mathematics Based on HOTS Questions). The module was evaluated by experts in content, Islamic integration, media, assessment, and practitioners. The overall validation results showed an average score of 92.4%, which falls into the